Heights of Cb clouds around Chhatrapati Shivaji International (C.S.I.) airport, Mumbai - Diurnal and seasonal variations - BISWAS, BIMAL KRISHNA (MAUSAM, 2006)
Lkkj & bl 'kks/k&i= esa 1990&99 ds o"kksZa ds nkSjku ekSle dk;kZy;] N=ifr f’kokth vUrjjk"Vªh; ¼lh- ,l- vkbZ-½ gokbZ vM~Ms esa ,df=r fd, x, jsMkj ds vk¡dM+ksa ds vk/kkj ij gokbZ vM~Ms ds lehi 200 fd- eh- dh ifjf/k esa 6 fd- eh- ls Åij vFkok blls vkSj vf/kd Å¡pkbZ ij QSys diklh es?kksa ¼lh- ch-½ dk v/;;u fd;k x;k gSA blesa lh- ch- lSyksa dh dqy la[;k ds ekSleh] ekfld vkSj ?kaVsokj forj.k vkSj mudh Å¡pkb;ksa] lh- ch- lfgr fnuksa dh la[;k] {kksHkeaMyh; lhek dh Å¡pkbZ rd igq¡pus okys lh- ch- lSyksa] foiqy lh- ch- es?kksa ds cuus ds izkFkfedrk okys LFkkuksa vkSj mudh xfr dh tk¡p djds mu ij fopkj&foe’kZ fd;k x;k gSA lh- ,l- vkbZ- gokbZ vM~Ms eqEcbZ ds lehi lh- ch- es?kksa ds fodkl ds fy, mÙkjnk;h flukfIVd fLFkfr;ksa dk Hkh irk yxk;k x;k gS vkSj mu ij fopkj&foe’kZ Hkh fd;k x;k gSA Based on radar data collected at the Meteorological Office, Chhatrapati Shivaji International (C.S.I.) airport, Mumbai during the years 1990-99, a study has been made on cumulonimbus (Cb) clouds with their height of top 6 km or more over an area having a radius of 200 km around the airport. The seasonal, monthly and hourly distribution of the total number of Cb cells and their heights, number of days with Cb, Cb cells that reached tropopause height, the preferred places of formation of large Cb clouds and their movement have been examined and discussed. The synoptic situation(s) responsible for the development of Cb clouds around C.S.I. airport, Mumbai have also been identified and discussed.